(untitled) (PERcursos Linguísticos, 2023)
This work has the following objectives: i. to report pedagogical actions carried out with Higher Education students, regarding the work with reading, understanding and interpretation of texts with the textual genre opinion article; ii. To propose reflections about the reading process, reading comprehension and textual interpretation skills carried out in the classroom. For this, the theoretical-methodological basis of the study is anchored in Textual Linguistics, from Koch (2002, 2014 and 2015), Koch and Elias (2012 and 2014), Marcuschi (2008) and Antunes (2003); in works on textual genres, from the perspective of clusters, based on Dolz and Schneuwly (2004) and on the problematizing question, by Freire and Faundez (1985), in addition to other scholars of the text, such as Carvalho (2018) and Bittencourt et al (2015). The results reveal an improvement in the cognitive, interactional and linguistic-textual skills of those involved. Finally, working with the opinion article, mainly through reading and understanding, enables greater interaction, reflection and awareness of the importance of improving students’ textual skills.